309 Food consumption and meal timing in hospital nurses with shift work: A preliminary study. (3rd May 2021) - Kim, Jee Hyun
Abstract: Introduction: One of the important nonphotic zeitgebers is food consumption. The timing of food consumption in relation to melatonin onset has been reported to be associated with fat proportion and BMI. Irregular meal timing along with irregular sleep schedules due to shift work would increase the metabolism problem as well as influencing sleep problems. The aim of the study is to evaluate the meal timing and food consumption in shift workers. Methods: The nurses with 3-rapid rotating shifts were enrolled to keep food diaries for two weeks including all three shift schedules. They filled out a morningness-eveningness questionnaire. They wore actigraphy to monitor sleep-wake patterns with a daily sleep diary. The timing and the frequencies of meal/snack and caffeine consumption during each shift and day-off were reviewed. The calorie from each food was calculated depending on the nutritional information on the internet. Results: 13 female nurses were screened and 6 finished the study. The mean age is 29.4±7.69 years and the mean body mass index was 20.2±1.1kg/m2. Average frequencies of meals are 2.59±0.49, 1.66±0.75, 1.93±0.41, 2.09±0.96 times per day, and average frequencies of snack consumption are 1.37±0.9, 1.07±0.74, 0.75±0.82, 0.96±0.79 times per day for the morning, evening, night, and the day off, respectively. Total calorie consumed are 1662.5±564.8, 1380.8 ± 940.3, 1596.8±838.1, 1505.8±706.9 kcals in the same order. Caffeine consumption was 0.29±0.46, 0.4±0.48, 0.72±0.65, 0.46±0.54 cups per day in the same order. One subject with morning type showed a relatively regular meal schedule throughout the shifts. The timing for main calorie consumption seemed to show delayed on evening and night shifts than morning shift although total calorie consumption was similar between each shift. Conclusion: Although this is a preliminary study with a small number of subjects, it showed shift worker nurses have an inconsistent number of meals and calorie intake depending on their shifts. Caffeine consumption is very lower than expected. The subject with morning chronotype seemed to keep relatively regular meal timing throughout the shifts, suggesting chronotype influences meal timing in shift workers. Support (if any): This study was supported by the National Research Foundation of Korea (NRF) grant funded by the Korea government (MSIT) (No.2019R1A2C1090643).